Experiences of being a former young carer: effects in the transition into adulthood and in the present life situation - Martin Nagl-Cupal; Sabine Metzing; Hanna Mayer (Revista Eletrônica de Enfermagem, 2015)
This qualitative study aims to describe the experiences of adults with caring responsibilities during their childhood. 16 semi-structured interviews with former young carers were conducted and analyzed using open and axial coding procedures and constant comparison techniques. Being responsible as a child in terms of caregiving has an impact on every person concerned. When entering adulthood, most former young carers maintain the responsibility for the ill person. They feel torn between the effort of trying to arrange their life in a different way and holding on to a life where responsibility is still a dominant concern. They remain silent about caregiving due to the fear of painful memories, or the inability to recognize themselves as former young carers. Knowledge of former young carers’ situation can improve the understanding of how caring shapes the transition into adulthood and can help to prevent an inappropriate caring role of actual caregiving children.